Arrhythmias as a Complication of Chemotherapy - Ergashov Bobir Bahodirovich (Scholars Digest Publishing, 2023)
The proposed review examines rhythm disturbances by the type of tachyarrhythmias, most often found in cancer patients, as well as their features, characteristic directly for oncological diseases, and emphasizes the importance of ECG monitoring for early diagnosis, treatment and monitoring of this cohort of patients who are more susceptible to the development of proarrhythmia. Oncologists should be fully aware of possible cardiac arrhythmias, and close cooperation between cardiologists and oncologists will lead to better stratification of the risk of developing cardiovascular diseases, monitoring and treatment.
Keywords: oncology, chemotherapy, arrhythmogenic effect, supraventricular tachycardia, ventricular tachycardia, cardioncology, cardiotoxicity.